Sistem Pakar Untuk Diagnosis Hama Pada Tanaman Jambu Air Menggunakan Metode Theorema Bayes - Yoga Junaedi; Betha Nurina Sari; Agung Susilo Yuda Irawan (Jurnal Ilmiah Informatika, 2020)
Technology is a tool or means used by humans to make ends meet. Technological development covers various aspects of life, such as health, education and in agriculture. One of the uses of current technological developments is the creation of expert systems. Expert systems in agriculture can help farmers in overcoming problems in their crops based on the symptoms that occur in these plants, so farmers can quickly find the right solution. One type of agricultural plants that are susceptible to various pests is water guava. In resolving pests and diseases that attack not a few of the farmers or owners make mistakes in overcoming the problems encountered. So by making an expert system to diagnose guava plant diseases it is expected to help farmers to overcome problems by providing good solutions. The process of making this expert system uses the Bayes theorem method. Bayes theorem method is one method to overcome the uncertainty of data. Where this method is based on the initial condition where the initial condition is a condition of existing symptoms then subject to predetermined rules then the greatest truth value is taken to determine the conclusions and solutions of the symptoms that have been mentioned previously.